Implementasi Pendidikan Profetik di Pondok Pesantren Kiai Mojo Tembelang Jombang - Ach. Saifullah; Imam Fuadi; Ahmad Tanzeh (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to describe prophetic education at the Kiai Mojo Tembelang Jombang Islamic Boarding School. A case study technique is employed in the qualitative research methodology. The findings revealed that there are three pillars of independence for students at the Kiai Mojo Tembelang Jombang Islamic Boarding School: independent worship, independent knowledge, and independent economy. The prophetic derivation is taken from Surah At-Taubah verse 128 and Ali Imran verse 110. The concept of humanization, which involves the nature of mercy, compassion, and amar maruf, is closely related to the independent pillar of knowledge to form students who have noble morals. The concept of liberation, which arises from a sense of heartlessness towards the suffering of humanity and then makes efforts to nahi munkar, plays an important role in forming santri who are committed to good deeds as an implementation of the economic independence pillar. The transcendent concept, which includes a strong desire to believe in Allah Swy and achieve the salvation of mankind, is related to the pillar of worship, which seeks to form santri to have tawhid awareness, maintain purity, and always think. Pondok Pesantren Kiai Mojo Tembelang Jombang internalizes the prophetic value in Surah At-Taubah verse 128 in a personal-individual context, then transforms it through the interpretation of Surah Ali Imran verse 110 in a communal-social context, in an effort to fulfill the goals of the greatest individuals (khoiru ummah).